Identification of Juvenile Delinquency Behavior in the City of Yogyakarta - Vicki Dwi Purnomo; Kelik Endro Suryono (PT FORMOSA CENDEKIA GLOBAL, 2023)
There is the phenomenon of juvenile delinquency which is increasingly prevalent in the city of Yogyakarta, various forms of juvenile delinquency ranging from mild delinquency such as truancy to delinquency that causes victims from other parties such as fighting, brawls and extortion. Juvenile delinquency behavior has various causative factors such as internal factors such as the child's weak self-defense from negative things and external factors such as from a less harmonious family, peers who have a negative influence on children. This is the basis for the purpose of this study, namely to find out the causes of the rise of juvenile delinquency that occurred in the city of Yogyakarta. Law enforcement officials and the government's role have made efforts, but there are often rampant acts of juvenile delinquency that occur in the city of Yogyakarta. The author identifies various sources to find out the causes of the rampant acts of juvenile delinquency.